Aflasafe SN01 is the first biocontrol product approved for aflatoxin mitigation in two nations, Senegal and The Gambia - Senghor, L.A.; Ortega Beltran, A.; Atehnkeng, J.; Jarju, P.; Cotty, P.J.; Bandyopadhyay, R. (Scientific Societies, 2021)
Aflatoxin contamination is caused by Aspergillus flavus and closely related fungi. In The Gambia, aflatoxin contamination of groundnut and maize, two staple and economically important crops, is common. Groundnut and maize consumers are chronically exposed to aflatoxins, sometimes at alarming levels, and this has severe consequences on their health and productivity. Aflatoxin contamination also impedes commercialization in local and international premium markets. In neighboring Senegal, an aflatoxin biocontrol product containing four atoxigenic isolates of A. flavus, Aflasafe SN01, has been registered and is approved for commercial use in groundnut and maize. We detected that the four genotypes composing Aflasafe SN01 are also native to The Gambia. The biocontrol product was tested during two years in 129 maize and groundnut fields and compared with corresponding untreated fields cropped by smallholder farmers in The Gambia. Treated crops contained up to 100% less aflatoxins than untreated crops. A large portion of the crops could have been commercialized in premium markets due to the low aflatoxin content (in many cases no detectable aflatoxins), both at harvest and after storage. Substantial aflatoxin reductions were also achieved when commercially-produced groundnut received treatment. Here we report for the first time the use and effectiveness of an aflatoxin biocontrol product registered for use in two nations. With the current scale-out and -up efforts of Aflasafe SN01, a large number of farmers, consumers, and traders in The Gambia and Senegal will obtain health, income, and trade benefits.